IDENTIFICATION OF CRITICAL LACTATION STAGE FOR THE BODY COMPOSITION IN MALE OFFSPRING OF HIGH-FAT FED DAMS - Maryana Debossan Fernandes; Ananda Malta; Letícia Ferreira Barbosa; Scarlett Rodrigues Raposo; Marcos Vinícius Martins; Gabriel Kian Guimarães Lopes; Douglas Lopes Almeida; Paulo Cezar de Freitas Mathias (Arquivos do Mudi, 2023)
Each stage (early, middle and late) of lactation is a critical period during which maternalmalnutritional can negatively effects on the offspring's body development. We investigatedthe effects of a maternal high fat diet (HF) during the different stages of lactation on bodyweight of male offspring at weaning. Female Wistar rats were fed either a HF diet only duringthe first week (HF1-7 group), second week (HF7-14 group), third week (HF14-21 group) andthroughout lactation (group HF1-21) or standard diet during all lactation. Biometricparameters of dams and male offspring were evaluated. HF fed dams did not have a differencein body weight, food intake and fat pad compared with the control dams. Regarding theoffspring, a higher final body weight was observed in males from the HF7-14 and HF14-21and HF21 groups compared to the control. There was an increase in retroperitoneal andmesenteric fat in HF21 and HF14-21 compared with control groups. Higher perigonadal fatpat was only observed in HF21. Consumption of maternal HF diet throughout lactation causeshigh body weight in male offspring. Interestingly, each isolated phase also causes importantbody weight accumulation, mainly the second and third week.